IMPROVING LEARNING THROUGH APPLICATION OF QUANTUM LEARNING TEACHING MODEL ON THE SUBJECT OF ADMINISTRATIVE PROCEDURE - Juliana Johan; Umi Widayastuti (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2013)
This study aims to increase studentâ€™s learning performance on â€œDoing Administration Procedureâ€ through the implementation of quantum teaching model. The action research was conducted with three cycle. Each cycle is formulated with four stages: planning, action, observation and reflections. This research shown that the implementation of quantum teaching model has got positive contribution in increasing studentâ€™s learning achievement.